The Effectiveness of Quranic Study Classes Online and In-Person: A Comparative Analysis at elHidayah Islamic Academy, Batu Belah Klang (Lembaga Contrarius Indonesia, 2026)
The face-to-face Quranic study approach is a traditional method that emphasizes the accuracy of recitation and the preservation of the authenticity of Quranic knowledge through the principles of talaqqī and musyāfahah. However, advances in digital technology and changing learning norms have expanded the use of online Quranic study classes as an alternative to the traditional in-person method. Therefore, this study aims to assess and compare the effectiveness of online and physical Quranic study classes at El-Hidayah Islamic Academy in terms of Quran reading ability, teacher teaching methods, and class implementation. This study employs a quantitative approach via a survey of 140 students from both online and physical Quranic study classes. The research instruments include a structured questionnaire and an oral reading test, while the data is analyzed using descriptive statistics and independent t-tests. The findings show significant differences in Quran reading ability, particularly in aspects such as the pronunciation of hijaiyyah letters, correct Quranic recitation, and mastery of Tajweed rules, with students in the online Quranic study classes recording higher mean test scores. However, no significant differences were found in teacher teaching methods or class implementation between the two modes of learning. This study concludes that online Quranic study can be effectively implemented when supported by strong pedagogical guidance from teachers and systematic oral assessment practices. Therefore, a hybrid approach is proposed to combine the advantages of both online and physical learning, ensuring that the effectiveness of Quranic study remains in line with the principles of talaqqī and musyāfahah in contemporary Islamic education.